PENYELESAIAN SENGKETA PENCATATAN PERALIHAN HAK ATAS TANAH TERHADAP TANAH YANG SEDANG DIBLOKIR - Hot Asih Hadi Wijaya, Ana Silviana, Agung Basuki Prasetyo (Diponegoro Law Journal, 2012)
Issues concerning common ground in people's lives, so that the problem of land disputes and eventually causes a lot of conflicts of interest among individuals. In Act No.5 of 1960 the Government instructed the registering of land to create legal certainty for the owner of the certificate of ownership of land.   The purpose of this study was to determine why the Land Office issued a Record of Surakarta on land inbetween being blocked consideration of judges and the Administrative Court in deciding the case if it is in accordance with the applicable national law of the land in Indonesia or not.   The method used is an empirical juridical approach, an approach that examines secondary data first, followed by studies of primary data in the field. Juridical factors are regulatory issues, especially land title deed and registration. Empirical factor is that people's behavior with regard to land registration and multiple certificates that occurred in the city of Surakarta. Analyzed descriptively to know the reason of the Land Office issued a Record Transition on land that is in a state judge blocked and consideration of the Administrative Court in deciding the case according to the law applicable national soil.   Results of research conducted to explain that the Land Office inaccurate in calculating the period of time that unblocking transition Registration issued when the land was still in a state judge blocked and consideration in issuing the decision was based on Article 126 item 2 PMA / Ka BPN on the ground blocking period.   The conclusion of this research is the Land Office land in violation of Article 126 block PMA / Ka BPN 3, 1997 regarding the blocking of the grace period time Padalah 30 (thirty) days after written request received by the Land Office block and the decision of the Administrative Court State for the actions of the Land Office was ordered to revoke the Land Office Records Letter No. Transitional Property Rights. 4045 Village Nusukan for violating the provisions of the national law of the land as set out in Article 126 item 2 PMA / BPN No Ka. 3 In 1997 the term of the ground blocking the blocking period.